Protein from fermented prawn waste silage as an ingredient in the diet of seabass - Nurzahwani Mohd. Nor, 1982-; Zainoha Zakaria, supervisor; Madihah Md. Salleh, supervisor; Mohamed Suhaimee Abd. Manaf; Fakulti Sains (2008)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2008